Antioxidant activity test of ethyl acetate fraction of binjai (Mangifera Caesia) leaf ethanol extract - K. Khairiah; Irham Taufiqurrahman; Deby Kania Tri Putri (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Binjai (Mangifera caesia) is a herb derived from South Kalimantan possessing antioxidant properties which promote wound healing inhibiting oxidation radicals. The natural antioxidants present in binjai leaves can be extracted by fractionation. Purpose: This study aimed to analyze the antioxidant activity of ethyl acetate fraction in 96% ethanol extract of binjai leaf. Methods: The study constituted a pure experimental study incorporating a post-test design with only random sampling technique consisting of two groups, namely; an ethyl acetate fraction as the treatment group and ascorbic acid as the positive control group. The leaves were treated in accordance with the soxhlet method and subsequently fractionated to extract ethyl acetate fraction. This was used to measure antioxidant activity with DPPH radical damping method using a UV-Vis spectrophotometer. A linear regression calculation was performed with a standard curve to quantify the IC50 value, before the ethyl acetate fraction underwent a qualitative test of secondary metabolite. Results: An independent t-test indicated significant differences between groups, an average value of IC50 in ascorbic acid of 13.812 ppm with 0.996 linearity and a fraction of ethyl acetate 38.526 ppm with a linearity of 0.999. In contrast, at this linearity value ascorbic acid and ethyl fraction acetate demonstrate a very high linear connection between concentration and inhibition. A secondary metabolite test conducted on the ethyl acetate fraction produced positive results for flavonoid, tannins, and phenol. Conclusion: Based on the IC50 parameters, the fraction of ethyl acetate in 96% ethanol extract of binjai leaf produces very strong antioxidant activity in the content of the compounds in the fraction, namely: flavonoid, tannins and phenol.